Does the Organizational Commitment Act as a Mediator of the Impact of the Organizational Culture and Compensation on the Performance of Employees? - Joko Sabtohadi (Jurnal Manajemen Indonesia, 2020)
The aim of this study was to examine the impact of organizational culture and compensation on the performance of employees and the indirect impact of organizational culture and compensation on the performance of employees through organizational commitment. Based on the study's goals, this study used a quantitative approach. Primary data collection analysis has been carried out using survey techniques. The study was conducted on 56 respondents who were Balitbangda workers, Kutai Kartanegara Regency. Review of the data used in this analysis using SEM-PLS. The results demonstrated the impact of the organizational culture, the compensation and the organizational commitment to the success of the business. Keywords—Organizational culture; Compensation; Organizational Commitment; Employee Performance